PENDIDIKAN DAN AKTIFITAS PELATIHAN PUSAT INKUBASI BISNIS USAHA KECIL (PINBUK) DI BAITUL MAAL wat TAMWIL (BMT) SULAWESI SELATAN - Muh Anwar; Nasrullah Nasrullah (UNIVERSITAS MUHAMMADIYAH MAKASSAR, 2019)
ABSTRACT This study aims to: (1) analyze the education of administrators / managers in the Syari'ah Baitul Maal wat Tamwil (BMT) Cooperative in South Sulawesi, (2) analyze PINBUK training activities and their role in growing and advancing the Baitul Maal Wat Syari'ah Cooperative Tamwil (BMT) in South Sulawesi, (3) analyze and assess the implementation of education and training (Diklat) organized by PINBUK in South Sulawesi. This study uses a qualitative method with a case study approach. The instruments used were field research which was carried out through in-depth interviews, field observations, literature studies and focus group discussions (FGD). The results show that education has an important role in administrators and managers of Baitul Maal wat Tamwil. This is based on the basic competencies to support performance, which is possible to obtain at a higher level of education. Even though it has an important role, its position is not absolute because these competencies can be developed through training activities. Of course, with heavier challenges due to the lack of a basis for competency development The training activities held by PINBUK are considered to be very determining the performance of BMT administrators and managers. This is based on the position of PINBUK Education and Training which is able to impart knowledge and skills, covering the required philosophical, conceptual and technical aspects, as well as motivation and belief to raise BMT together. BMT which intensively follows PINBUK Training and Education has proven to be able to maintain its existence and continue to develop from time to time. Furthermore, PINBUK is considered capable of organizing training that meets the main components of success. But still on a minimum scale, development is needed to produce the maximum results. Keywords: Baitul Maal wat Tamwil (BMT), PINBUK, Islamic Economics, Education Level, and Education and Training (Diklat).